The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1537/asj.114.35
|View full text |Cite
|
Sign up to set email alerts
|

The Morphology of Maxillary Sinus in Modern Japanese with the Use of CT Image

Abstract: 平成 17 年 5 月 2 日受付,平成 18 年 4 月 14 日受理 ) 要 約 本研究は頭蓋の X 線 CT(Computed Tomography)画像から上顎洞の形態やサイズを計測し,分析を行 なったものである。近代日本人女性乾燥頭蓋 42 体 84 側(平均年齢 38.9 歳)を資料として,CT 装置による 撮影を行ない,得られた画像から画像解析ソフトによる上顎洞の前後径,高径,幅径,体積の計測を行な い,本研究と同様の機器・手法で行われた同時代の日本人男性乾燥頭蓋に関する計測結果(野木・金澤, 2001; 野木,2002)との比較を行なったところ,前後径,高径,体積の各項目において,男性の上顎洞よ りも女性の上顎洞のほうがサイズは小さかった。主成分分析を行ったところ,上顎洞の大きさの変異は第 1 主成分のサイズファクターで説明されることがわかった。頭蓋の直接計測値との相関については,体積 が顔長,頭蓋最大幅,上顔高との正の有意な相関があり,前後径と頭蓋最大長,高径と顔長に有意の相関 がみられた。上顎洞底部の形態を大きく 3 つのタイプ, 「ラウンド型」 「フラット型」 「イレギュラー型」に 分類したと… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The phyletic importance and function of the sinus floor morphology is uncertain, as the degree of the sinus penetration can be highly variable within a primate genus or even species (for example, Australopithecus afarensis, Sivapithecus, Homo sapiens). [54][55][56] Recent studies on the maxillary sinus in living and fossil anthropoids have indicated that the presence/absence of the sinus can involve a significant amount of homoplasy. [57][58][59][60] The hard palate of N. kerioi is shallow, a common condition for East African Miocene hominoids.…”
Section: Cranium and Dentitionmentioning
confidence: 99%
“…The phyletic importance and function of the sinus floor morphology is uncertain, as the degree of the sinus penetration can be highly variable within a primate genus or even species (for example, Australopithecus afarensis, Sivapithecus, Homo sapiens). [54][55][56] Recent studies on the maxillary sinus in living and fossil anthropoids have indicated that the presence/absence of the sinus can involve a significant amount of homoplasy. [57][58][59][60] The hard palate of N. kerioi is shallow, a common condition for East African Miocene hominoids.…”
Section: Cranium and Dentitionmentioning
confidence: 99%